ANALYSIS OF PREFERENCE FUNCTION BY CAR IN THE CITY OF SYDNEY, AUSTRALIA - Suthanaya, Putu Alit (Jurnal Ilmiah Teknik Sipil, 2012)
One important aspect in the sustainable transportation target is the reduction in vehicle kilometres of travel (VKT) by car. The use of private car is one major contributor of environmental deterioration in Sydney. It is essential to understand the journey-to-work travel behaviour by car. One of the method that can be used to study this travel behaviour is preference function. Using journey-to-work (JTW) Census data over a 35-year period from 1961 to 1996 in Sydney, this paper applies preference functions to study the journey-to-work commuting preferences by car. Descriptive statistics and analysis of variance are applied to evaluate the trends in the slope preferences over time. Moran’s I statistic of spatial association is used to study the spatial distribution of preference functions, and the pattern of interactions between zones, to assess the level of interaction and to test their statistical significance. The results indicated that the mean slope preference by car has increased over time showing an increasing preference of residents towards distance maximization for traveling to work by car. The slope preferences by car for the inner and middle ring residents are relatively stable over time whilst the outer ring residents (beyond 20 km from the CBD) experienced a dramatic increase. Mostly, the zonal slope preferences by car in Sydney in 1996 were within one standard deviations of the mean. Only Parramatta (30) was found to have a value of over two standard deviations of the mean on the maximization side. It is clearly shown from these results that when increasing job opportunities are available in the surrounding zones, residents tend travel longer to reach job opportunities available in the other zones, in particular, in the case of job-skill mismatch. Therefore, it is not surprising that a dramatic increase in preference for longer trips has been experienced by outer ring residents in Sydney where job decentralization continues to occur over time.
Keywords: preference function, travel behaviour, private car.